2000
DOI: 10.1002/(sici)1097-0290(20000205)67:3<372::aid-bit14>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Production of tomato flavor volatiles from a crude enzyme preparation using a hollow-fiber reactor

Abstract: In recent years there has been an increase in the interest in the production of compounds by isolation from natural sources or through processes that can be deemed “natural”. This is of particular interest in the food and beverage industry for flavors and aromas. Hexanal, organoleptically known to possess “green character”, is of considerable commercial interest. The objective of this study was to determine if the enzyme template known to be responsible for the synthesis of hexanal from linoleic acid (18:2) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 16 publications
2
16
0
Order By: Relevance
“…r The application of enzymatic methods to obtain food ingredients, such as the production of tomato aroma (hexanal) using a hollow-fiber reactor (with and enzyme template extracted from ripe tomato fruits) (Cass et al, 2000).…”
Section: Foods Enriched With Natural Ingredientsmentioning
confidence: 99%
“…r The application of enzymatic methods to obtain food ingredients, such as the production of tomato aroma (hexanal) using a hollow-fiber reactor (with and enzyme template extracted from ripe tomato fruits) (Cass et al, 2000).…”
Section: Foods Enriched With Natural Ingredientsmentioning
confidence: 99%
“…Tomato flavour enzymes were harnessed as a crude enzyme preparation in a commercial ultrafiltration unit, operated as a hollow-fibre reactor to produce hexanal from linoleic acid (Cass et al, 2000). The reactor proved to be stable over an operation period of 5 days, indicating that flavour production with immobilised membrane-associated enzymes in a hollow-fibre reactor is a promising technique.…”
Section: Process Developments Of Plant Catalystsmentioning
confidence: 99%
“…This behavior is analogous to that of a pure substance in a ultra-filtering system (Tejada, 1995). A straight-line trend is identified by Luque et al, (1999) and by Cass et al, (2000), while assessing hollowed-fiber membrane modules. Therefore, the lines presented as trends in the graphics are adjusted to a straight line.…”
Section: Trans-membrane Pressurementioning
confidence: 99%
“…Organic phase separation as of the biosulfurization reaction's emulsion, at different cellular concentrations and at a 25:75 organic/watery phase ratio explains the decrement of permeability flux observed by comparing hexadecane, diesel and emulsion. Cass et al, (2000) reported a reduction in the permeability flux along against transmembrane pressure decrease due to the components present in the enzymatic raw extract used. Figure 4 shows a schematic diagram for the bioreactor's operation.…”
Section: Trans-membrane Pressurementioning
confidence: 99%
See 1 more Smart Citation